Expanding the genetic code: a non-natural amino acid story. (10th March 2023) - Zitti, Athena; Jones, Dafydd
Abstract : From enzymes to hormones, proteins are the most versatile macromolecules that serve a vital function throughout all biological systems. In nature, organisms are restricted to a 20 amino acid repertoire, which in turn limits the chemistry. Nature evolves and adapts but currently does so under a "chemistry-limited" circumstance. This in turn has limited the aspirations of protein designers and engineers that aim to expand the functional and structural properties of proteins into new and exciting realms. One way nature has circumvented this problem is to recruit non-proteinaceous cofactors. Another way is to change one of the most fundamental concepts underlying biology: the genetic code. Pyrrolysine and selenocysteine are the two main genetically encodable proteinogenic "21st" amino acids; stop codons are recruited to encode the incorporation during ribosomal polypeptide synthesis. This ability of nature to go beyond the standard 20 amino acid repertoire inspired researchers to engineer the fundamental elements of ribosomal polypeptide synthesis and allow full genetic encoding of non-natural amino acids. This in turn helped advance synthetic biology and protein engineering in ways that were not possible by using the standard 20 amino acids. To this day, a vast repertoire of non-natural amino acids is available and is continuously expanding with increasing scientific needs.